PEMILIBAN DAN PENGGUNAAN MEDIA DALAM PROSES PEMBELAJARAN - Sungkono, Sungkono (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Learning media is an essential factor in improving learning quality. 'n using media in learning process, educators must be selective in choosing the kind of media she/he will use. The criteria ones must pay attention in choosing learning media are: learning purpose, effectivenes:;, student characte.-istics, availability, technical quality, flexibility, user skill and available time. The steps in choosing learning media are 1) learning activity 2) message delivery 3) subject characteristics 4) media cla.!>sijication 5) media characteristics analysis. There are two models in using /earning media: inside class and outside class. The procedures in using learning media are preparation, implementation and follow up.